Computer-based learning: E-Learning - Bih Ni Lee (Sakarya University, 2017)
This article discusses how the computer-based e-learning is useful and practical in life today. Researcher has used literary narrative research to build the foundation of scientific knowledge. Researcher has collected all the important points in the discussion and put them in here with reference to the specific areas in which this paper was originally based. The results showed that someone who cannot follow conventional education because of various causes, for example time constraint, geographical constraints, physical constraints, limited available seats, phobia of school, dropout, or home schoolers possible to be able to keep learning through e-Learning. Electronic learning (e-Learning) related to meeting with online learning or computer-based learning. In the future the application of Internet technology in the field of education and training will be needed in order to improve quality and equity of educational services, especially in Malay Archipelago whose territory is scattered in very remote areas.